An analysis of e-insurance as a cost cutting method : a case of RM Insurance Pvt Ltd - Musindo, Claudius (Midlands State University, 2017)
The study is about an analysis of e-insurance as a cost cutting method at RM Insurance in Harare. The study made an examination into the effectiveness of this model as employed by RMI. The research made use of a case study design and henceforth interviews and questionnaires were used to gather data. The results showed that e-insurance was not reducing underwriting costs as anticipated due to various factors. However, it was noted that the model yielded some positives in the operations of RMI. Recommendations made to the company include its needs to extend its costs focus by using the model in its entirety to reduce other costs like advertising through e-marketing, developing a Shared multichannel for policy distribution, continuous training of employees, developing sound published security policy and establishing a steering committee to be in charge of training.